Cost effectiveness of interferon α or peginterferon α with ribavirin for histologically mild chronic hepatitis C. Issue 9 (30th June 2005) - Grieve, R; Roberts, J; Wright, M; Sweeting, M; DeAngelis, D; Rosenberg, W; Bassendine, M; Main, J; Thomas, H
Abstract : Background: For patients with mild chronic hepatitis C the cost effectiveness of antiviral therapy is unknown. Aims: To assess whether antiviral therapy (either interferon α or peginterferon α combined with ribavirin) is cost effective at a mild stage compared with waiting and only treating those cases who progress to moderate disease. Patients: Cases with mild chronic hepatitis C. Methods: A cost effectiveness model which estimates long term costs and outcomes for patients with mild chronic hepatitis C. The model uses effectiveness and cost data from the UK mild hepatitis C randomised controlled trial, combined with estimates of disease progression and cost from observational studies. Results: Antiviral treatment at a mild rather than a moderate stage improved outcomes measured by quality adjusted life years (QALYS) gained. The mean cost per QALY gained from antiviral treatment with interferon α-2b and ribavirin, compared with no treatment at a mild stage, was £4535 (7108) for patients with genotype non-1 and £25 188 (39 480) for patients with genotype 1. Providing peginterferon α-2b and ribavirin at a mild rather than a moderate stage was also associated with a gain in QALYS; the costs per QALY gained were £7821 (12 259) for patients with genotype non-1 and £28 409 (44 528) for patients with genotype 1. Conclusions: For patients with chronic hepatitis C, it is generally more cost effective to provide antiviral treatment at a mild rather than a moderate disease stage. For older patients (aged 65 years or over) with genotype 1, antiviral treatment at a mild stage is not cost effective.